2022
DOI: 10.1101/2022.03.22.485233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Context-dependent triggering of STING-interferon signaling by CD11b agonists supports anti-tumor immunity in mouse models and human cancer patients

Abstract: Chronic activation of inflammatory pathways and suppressed interferon signaling are hallmarks of myeloid cells in immunosuppressive tumors that drive poor responsiveness to conventional and immune therapies. Previous studies have identified agonistic activation of the CD11b integrin as a potential strategy to enhance anti-tumor immunity. However, the mechanisms by which CD11b-agonism reprogram tumor immunity are poorly understood, and this may impair patient selection and identification of effective treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Formation of the Atg5-Atg12-Atg16L complex, located on the outside of the phagophore membrane, recruits light chain 3 (LC3) for processing and maturation in the next stage ( 3 ). Microtubule-associated protein LC3 is processed into a lipidated form (LC3 lipidation) and inserted into the extending phagophore membrane, leading to the maturation of the autophagosome ( 4 ). The autophagosome captures the material to be degraded, which can be either random or selective ( 5 ).…”
Section: Molecular Mechanisms Of Cgas-sting-mediated Inflammation Met...mentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of the Atg5-Atg12-Atg16L complex, located on the outside of the phagophore membrane, recruits light chain 3 (LC3) for processing and maturation in the next stage ( 3 ). Microtubule-associated protein LC3 is processed into a lipidated form (LC3 lipidation) and inserted into the extending phagophore membrane, leading to the maturation of the autophagosome ( 4 ). The autophagosome captures the material to be degraded, which can be either random or selective ( 5 ).…”
Section: Molecular Mechanisms Of Cgas-sting-mediated Inflammation Met...mentioning
confidence: 99%
“…Activation of STING plays a crucial role in defending against pathogen invasion and promoting anti-tumor immunity. For instance, STING activation can induce cellular senescence, promote dendritic cell maturation, and other mechanisms to exhibit anti-tumor effects (3,4). Studies using STING agonists alone or in combination with other drugs have shown promising results, such as the use of STING agonist DMXAA in combination with chemotherapy drug SN38, which demonstrated strong antitumor effects in melanoma and colon cancer (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%